(untitled) (American Journal of Physical Education and Health Science, 2025)
The study aims at preparing specific exercises on both sand and grass training surfaces of tennis players, and investigating the effect of these exercises on the transitional speed of tennis players. To achieve the study’s aims, 12 tennis players were randomly chosen to be the study’s sample. Two groups were enrolled in this experiment, (6) tennis players in the experimental group and the same number in the control group. Special transitional speed exercises on both sand and grass surfaces, were applied to the experimental group, using four training sessions per week for eight weeks. The results show a significant effect on the transitional speed test results for the experimental group. The major conclusion was that implementing specific exercises on different training surfaces (sand and grass) prepared by the researcher had a positive effect on transitional speed.